Детекторные свойства Cd₀,₉Zn₀,₁Te:Al под влиянием гамма-облучения малой дозы - Кондрик, А.И. (Технология и конструирование в электронной аппаратуре, 2016)
Проведен анализ и указаны возможные причины изменений характеристик глубоких уровней в высокоомном Cd₀,₉Zn₀,₁Te:Al после γ-облучения и в течение пострадиационной релаксации. Исследована зависимость свойств плоскопараллельного детектора на основе Cd₀,₉Zn₀,₁Te:Al от концентрации и уровня энергии глубокого донора, а также от степени легирования алюминием. Определены условия деградации регистрирующих свойств детектора на начальном этапе его эксплуатации под воздействием агрессивной радиационной среды. Проведено аналіз та вказано можливі причини змін характеристик глибоких рівнів у високоомному Cd₀,₉Zn₀,₁Te:Al під час γ-опромінення та протягом пострадіаційної релаксації. Досліджено залежність властивостей плоскопаралельного детектора на основі Cd₀,₉Zn₀,₁Te:Al від концентрації та рівня енергії глибокого донора, а також від ступеня легування алюмінієм. Визначено умови деградації реєструвальних властивостей детектора на початковому етапі його експлуатації під впливом агресивного радіаційного середовища. Clarification of the influence of defects on detecting properties of CdZnTe detectors and understanding of the behavior of defects under the influence of aggressive radiation environment are very important to improve detector performance. The objective was to study the charges collection efficiency and the resistivity of Cd₀,₉Zn₀,₁Te:Al detectors operating under the influence of low dose γ-radiation. The study was carried out by computer simulation, where initial data were provided by the experiment results of other researchers. The possible reason for the change of measured signatures of defect levels in high resistance Cd₀,₉Zn₀,₁Te:Al during gamma irradiation and 1 month later is the change in compensation degree of the material. The changes in the properties of Cd₀,₉Zn₀,₁Te:Al detector have been researched depending on the concentration and energy level of the deep donor for different concentrations of deep acceptors, as well as on the degree of alloying with aluminum. The negative factor for registering properties of Cd₀,₉Zn₀,₁Te:Al detector is increased concentration of zinc vacancies, which may arise at manufacturing stage and under influence of γ-irradiation during operation. The degradation of properties of irradiated detector may occur due to the offset dependence of the resistivity on the aluminum dopant concentration N(Al) towards to higher concentrations of Al when the value of doping is not enough large. Only resistivity will be reduced and charge collection efficiency may increase. The increase in resistivity of Cd₀,₉Zn₀,₁Te and charges collection efficiency of the detector occur when there is a sufficiently high level of doping the material with aluminum.